Attitude and Awareness towards Information and Communication Technology of Student-Teachers - Nithyanantham, Vinnaras; N. , Rekha (International Journal of Psychosocial Rehabilitation, 2020)
This article is based on the attitude and awareness towards information and communication technology in their teaching and learning environment. A survey was conducted at the different teacher training colleges in Tiruchirappalli district, located in Tamil Nadu, India, and the student-teachers studying in teacher training colleges were the sample. This investigation may help the teacher educators and the curriculum constructors to concern themselves with the development of the ICT skills and attributes that are vital for the formation of teachers in modern society. Some alterations and enhancements of student-teachers current knowledge and skills in order to include important awareness and attitudes about the ICT environment and sustainable development are suggested and discussed in this article.